Do Workload, Burnout, and Work Environment Predict Employee Performance Among Public Servants? - Dhanang Wahyu Widiarso; Tatik Mulyati; Mohammad Sofyan (Citakonsultindo, 2026)
Public service performance has remained a major concern due to its direct impact on community satisfaction and regional development. While studies have addressed the technical and infrastructural factors as the cause of poor public service delivery, studies addressing the psychological and environmental human factors seem sketchy. Therefore, this study examines the predictive role of workload, burnout, and work environment on employee performance among public servants at the Department of Transportation in Ngawi Regency, East Java, Nigeria. A cross-sectional survey design was adopted, while a proportionate stratified random sampling technique was used to select the study population. Validated questionnaires were used to collect data from 109 participants and analyzed using multiple linear regression to test the hypothesis, which was accepted at the p < .05 level of significance. The result demonstrated that the independent variables significantly correlated with employee performance among the study participants, R² = .754, F (3,105) = 12.228, p < .001. Furthermore, workload (β = -.197, p = .042) and burnout (β = -.123, p = .028) negatively predicted performance, whereas the work environment (β = .328, p = .040) positively and dominantly predicted employee performance. The study concludes that human and environmental factors significantly contributed to performance fluctuations among the study participants. The study recommends all stakeholders take proactive measures to upgrade the physical work environment and checkmate excessive workloads to mitigate burnout and optimize public service delivery.